The relationship between hypertensive disorders in pregnancy and endometriosis: a systematic review and meta-analysis - Foruzan Sharifipour; Zaynab Mohaghegh; Zahra Javanbakht; Shahla Faal Siahkal; Faeze Azizi (BMC, 2024)
Abstract Background Endometriosis is a chronic and debilitating disease that can affect the entire reproductive life course of women, with potential adverse effects on pregnancy. The aim of the present study is to investigate the association between hypertensive disorders in pregnancy and endometriosis. Method Relevant articles were searched from the Cochrane Library, PubMed, Scopus and Web of Science from inception up to December 2023. The full-text observational studies published in English that had a confirmed diagnosis of endometriosis were included. The case group included pregnant women diagnosed with endometriosis at any stage, while the control group consisted of pregnant women who had not been previously diagnosed with endometriosis. Two authors extracted and analyzed the data independently. Disagreements were reconciled by reviewing the full text by a third author. Endnote X9 was used for screening and data extraction. We used fixed and random effects models in Review Manager 5.3 to analyze the pooled data. The quality of the included studies was assessed using the Downs and Black checklist. Results Out of the 9863 articles reviewed, 23 were selected for meta-analysis. According to the results of this study, there was an association between endometriosis and gestational hypertension (OR = 1.11, 95% CI: 1.06, 1.16; I 2 = 45%, P < 0.00001; N = 8), pre-eclampsia (OR = 1.26, 95% CI: 1.18, 1.36; I 2 = 37%, P < 0.00001; N = 12), and hypertensive disorders in pregnancy (OR = 1.13, 95% CI: 1.06, 1.21; I 2 = 8%, P = 0.0001; N = 8). Conclusions This study confirmed that endometriosis may elevate the risk of developing gestational hypertensive disorders. Raising awareness of this issue will help to identify effective strategies for screening and early diagnosis of hypertensive disorders in pregnancy.